DETERMINANTS OF CUSTOMERS IN SELECTING SHARIA BANKING SYSTEM FOR SAVING IN EAST JAVA - INDONESIA - Joko Mariyono (Universitas Hayam Wuruk Perbanas, 2013)
Sharia banks have been developing in many countries since the evidence that the banks were more resistant to financial shocks. In Indonesia, Sharia banks have a good environment because majority of Indonesian people is Muslim. During recent years, Shariabanking inIndonesia shows a dramatic growth. This paper is to examine internal factors affecting customers’ decision to choose Sharia banking systemas a place of saving. Logit regression was used to estimate a model of customers’ decision. Cross-sectional data, consisting of101 Sharia customers and 110 conventional customers, were randomly drawn from database of a multinational bank that provides both Sharia and conventional schemes. The results show that age, gender and religion led to customers more likely to invest their money in Sharia scheme. In contrast, income, entrepreneur and student led to customers less likely to choose Sharia scheme as a place of investment. Highest positive impact came from religion, and highest negative impact came from student. Even though the majorityof Indonesian people are Muslim, the total possibility of people to select Sharia scheme was low.